PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS GENIALLY TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS IV MATA PELAJARAN IPAS DI SD N PRENGGUK II - Alvian Nurfaizah, Asfi; Suwartini, Sri; Melani Ika Susanti, Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning interest of students in Natural and Social Science (IPAS) subjects is a problem that needs to be addressed through more engaging and interactive learning innovations. This study aims to determine the effect of Genially-based learning media on the learning interest of fourth-grade elementary school students in the plant body parts topic. This study employed a quantitative approach with a Quasi Experimental Design and Nonequivalent Control Group Design. The subjects consisted of 50 students divided into two groups: the experimental class at SD Negeri Prengguk II using the Problem Based Learning (PBL) model with Genially media, and the control class at SD Negeri 1 Kadibolo using PBL with a scientific approach. Data were collected through a learning interest questionnaire using a four-point Likert scale covering aspects of enjoyment, attention, involvement, and interest. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, Levene's homogeneity test, and Independent Samples T-Test with SPSS version 27.0. The results showed that the data were normally distributed and the variances were homogeneous. The Independent Samples T-Test revealed a Sig. (2-tailed) value of < 0.001 with a mean difference of 18.920 points, indicating a significant difference between the two groups. The mean learning interest score of the experimental class (85.28) was significantly higher than the control class (66.36). Therefore, Genially-based learning media is proven effective in improving the learning interest of fourth-grade elementary school students in IPAS subjects.